The evolution of forest coverage: Wood trade and its impact on forest functions - Aurel Lup; Ana Ursu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
The material presents the problem of forests, deforestation becoming nowadays a real global problem of mankind. Many millennia ago, population growth required the sacrifice of the forest to make way for crops, today forests are cut primarily for profit, wood being one of the most precious commodities. It is true that in some parts of the world the forest is also sacrificed to increase the arable area. In countries like Romania, for example, both legal and especially illegal logging is done only for money, wood being over 10 times more expensive than any other agricultural product. The consequences of deforestation on many functions performed by the forest are evaluated, such as: carbon dioxide absorption and oxygen release, recreation function, preventing soil erosion with serious consequences on its quality, but also floods, floods, inhabited areas, roads transport and other objectives. The material also tries an evolution in time of the phenomenon both in Romania and globally.
Keywords: Q13; Q27; 330; forest; wood; deforestation; profit; erosion